2022
DOI: 10.1029/2022jc018874
|View full text |Cite
|
Sign up to set email alerts
|

Ocean Mixed Layer Response to Two Post‐Monsoon Cyclones in the Bay of Bengal in 2018

Abstract: The Bay of Bengal (BoB) is characterized by a shallow (∼10–20 m deep) fresh layer associated with 40–60 m deep warm near‐surface layer during the post‐monsoon season (October–November). We use hourly observations from a moored buoy at 15°N, 90°E along with satellite and ocean analysis data sets to understand the evolution of the near‐surface layer during the passage of two category‐3 cyclonic storms: Cyclone Titli (7–11 October 2018) and cyclone Gaja (10–15 November 2018). The mooring was ∼200 km away to the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
(89 reference statements)
1
4
0
Order By: Relevance
“…TC-induced warming accounted for approximately 14% of the total locations, which aligns with findings reported by other researchers [44,60,61]. The study further identified that warming events typically occurred in the latitude range of 8 • -15 • N (Figure 6).…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…TC-induced warming accounted for approximately 14% of the total locations, which aligns with findings reported by other researchers [44,60,61]. The study further identified that warming events typically occurred in the latitude range of 8 • -15 • N (Figure 6).…”
Section: Discussionsupporting
confidence: 90%
“…When TC-induced mixing occurs, the subsurface warm layer is mixed up, resulting in an increase in SST [20]. Previous studies using in situ measurement and numerical models have extensively investigated this feature and have shown that when mixing introduces subsurface warm water to the surface, there is no cold wake phenomenon [61]. The existence of the pre-storm subsurface warm layer has been confirmed through mooring observations during the passage of TC Phailin [63].…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…In 2018, a low‐pressure system developed in the Arabian Sea, followed by monsoon depressions and caused heavy rainfalls and flash floods over Kerala. Further, a Very Severe Cyclonic Storm Gaja in November 2018 passed through the close vicinity of the study region (George et al, 2021; Jarugula & McPhaden, 2022). In 2019, similar conditions occurred when a Very Severe Cyclonic Storm Vayu in June 2019 and an Extremely Severe Cyclonic Storm Maha in October 2019 (Mishra et al, 2021) impacted the study region.…”
Section: Resultsmentioning
confidence: 99%